Fast, silent self-stabilizing distance-k independent dominating set construction - Johnen, Colette (Information processing letters, 2014)
We propose a fast, silent self-stabilizing protocol building a distance-k independent dominating set, named FID. The convergence of the protocol FID is established for any computation under the unfair distributed scheduler. The protocol FID reaches a terminal (also legitimate) configuration in at most 4n+k rounds, where n is the network size; it requires (k+1)log(n+1) bits per node. •The protocol FID builds in self-stabilizing manner distance-k independent dominating sets.•The protocol FID is silent, fast and simple.•The protocol FID works properly under any schedule.•The correctness and the termination of the protocol FID is proven.•The convergence time to reach a legitimate configuration is established: 4n+k where n is the network size.